DIGITIZATION OF OLIGARCHY: THE TRANSFORMATION OF POWER IN THE DIGITAL LANDSCAPE - Meiyani, Eliza; Kosasi, Rindi; Younus, Muhammad (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
This study aims to investigate how oligarchy in power politics and economics affects people's welfare, especially in the context of the dominance of digital oligarchy and the challenges that arise in dealing with this inequality of power. Using qualitative research methods, data were collected through literature reviews from various validated journals, articles, websites, and mass media news. The findings of the study show that the dominance of major digital platforms by digital elites strengthens socio-economic inequality in Indonesia. Data evidence shows that platforms such as WhatsApp (90.9), Instagram (85.3), and Facebook (81.6) have high usage rates, allowing for information control and manipulation of public opinion. This exacerbates injustice, with the richest 1% of the population having an average wealth of more than 2000, while the poorest 50% of the population only have an average wealth of $6.34. This study suggests increasing digital literacy, strict regulations, and diversifying information sources as strategic steps to reduce the dominance of digital oligarchs and ensure a more equitable distribution of power in the digital era.gb777